Comparison of the Moonlighting Actions of the Two Highly Homologous Chaperonin 60 Proteins of Mycobacterium tuberculosis - Cehovin, Ana (American Society for Microbiology (ASM), 2010)
Evidence is emerging that the two chaperonin (Cpn) 60 proteins of Mycobacterium tuberculosis, Cpn60.1 and Cpn60.2, have moonlighting actions that may contribute to the pathology of tuberculosis. We studied the release of Cpn60.1 from M. tuberculosis and infected macrophagelike cells and compared recombinant Cpn60.1 and Cpn60.2 in a range of cell-based assays to determine how similar the actions of these highly homologous proteins are. We now establish that Cpns are similar as follows: (i) Cpn60.1, as it has been shown for Cpn60.2, is released by M. tuberculosis in culture, and Cpn60.1 is furthermore released when the bacterium is in quiescent, but not activated, macrophagelike cells, and (ii) both proteins only showed a partial requirement for MyD88 for the induction of proinflammatory cytokine production compared to lipopolysaccharide. However, we also found major differences in the cellular action of Cpns. (i) Cpn60.2 proved to be a more potent stimulator of whole blood leukocytes than Cpn60.1 and was the only one to induce tumor necrosis factor alpha synthesis. (ii) Cpn60.1 bound to ca. 90% of circulating monocytes compared to Cpn60.2, which bound <50% of these cells. Both chaperonins bound to different cell surface receptors, while monocyte activation by both proteins was completely abrogated in TLR4(−/−) mice, although Cpn60.2 also showed significant requirement for TLR2. Finally, an isogenic mutant lacking cpn60.1, but containing intact cpn60.2, was severely inhibited in generating multinucleate giant cells in an in vitro human granuloma assay. These results clearly show that, despite significant sequence homology, M. tuberculosis Cpn60 proteins interact in distinct ways with human or murine macrophages.